Does the product quality hypothesis hold true? Service quality differences between independent and exclusive insurance agents - Lucinda Trigo Gamarra (Universität Rostock, Institut für Volkswirtschaftslehre, 2007)
Insurance products are distributed both by independent and dependent agents, although the use of independent agents is more costly. The product quality hypothesis states that independent agents provide both insurers and customers with higher service quality and therefore, remain on the market. On the contrary, according to the market imperfections hypothesis both intermediary types offer the same quality, and only coexist due to information asymmetries. Having conducted a written survey, we measure service quality differences by multivariate regression analysis. Our analysis shows that the higher level of service quality of independent agents supports the product quality hypothesis. The result is a separating equilibrium on the market.
Keywords: G22; L15; L22; 330; Insurance intermediation; service quality; distribution systems; Versicherungsvermittlung; Dienstleistungsqualität; Versicherung; Vertriebsweg; Vergleich; Schätzung